Roth Music Cocoon MC4 better sound from a vacuum. - Curthoys, Paul.
Roth's vacuum tube amp improves iPod tunes...most of the time.
Keywords: Vacuum tubes; Vacuum tube amplifier; Digital music; Amplifiers